Antimicrobial peptide AP2 ameliorates Salmonella Typhimurium infection by modulating gut microbiota - Lianglan Li; Qiufen Mo; Yi Wan; Yuanhao Zhou; Weiqin Li; Weifen Li (BMC Microbiology)
Abstract Background Endogenous antimicrobial peptides and proteins are essential for shaping and maintaining a healthy gut microbiota, contributing to anti-inflammatory responses and resistance to pathogen colonization. Salmonella enterica subsp. enterica serovar Typhimurium (ST) infection is one of the most frequently reported bacterial diseases worldwide. Manipulation of the gut microbiota through exogenous antimicrobial peptides may protect against ST colonization and improve clinical outcomes. Results This study demonstrated that oral administration of the antimicrobial peptide AP2 (2 µg /mouse), an optimized version of native apidaecin IB (AP IB), provided protective effects against ST infection in mice. These effects were evidenced by reduced ST-induced body weight loss and lower levels of serum inflammatory cytokines. A 16 S rRNA-based analysis of the cecal microbiota revealed that AP2 significantly modulated the gut microbiota, increasing the relative abundance of Bifidobacterium while decreasing that of Akkermansia at the genus level. Furthermore, the transplantation of fecal microbiota from AP2-treated donor mice, rather than from Control mice, significantly reduced cecal damage caused by ST and decreased the concentration of ST by one order of magnitude after infection. Conclusions These findings reveal a novel mechanism by which exogenous antimicrobial peptides mitigate Salmonella Typhimurium infection through the modulation of gut microbiota.